Contingent Contradictions and the (Il)Logics of Adolescence: Examining How Undergraduates in an LGBTQ+ Young Adult Literature Course Read Queer Youth - Smith, Kyle P.; Wargo, Jon M. (Reading research quarterly, 2025)
This article explores how undergraduate students enrolled in a postsecondary course centering LGBTQ+ young adult literature came to discursively construct notions of queer youth. Braiding postdevelopmental and poststructural theories of childhood with queer theory, we interrogated how what we name as the (il)logics of adolescence shaped who and what queer youth, as a construct, was and could be for participants. Reading across classroom artifacts and student talk about texts, our findings highlight the shifting and multiple (il)logics offered by students as they attempted to unsettle understandings of queer youth in conjunction with course novels. In particular, we examine how two constitutive theories—homonormativity and chrononormativity—generated both contingent and contradictory moments wherein the subject of the queer child was both regulated and liberated by participants. Offering implications that expand understandings in both the reading and teaching of queer young adult literature, the study closes by discussing this particularly contentious moment, noting possibilities in how LGBTQ+ adolescents can and cannot be rendered and understood through stories of youth. This study examines how undergraduates in an LGBTQ+ young adult literature course read queer youth, highlighting the contingencies and contradictions of youth ‐ as a concept ‐ and the power of literature to shape our understanding of the world